Sensitivitas Makroekonomi dan Moneter Terhadap IHSG - Reza Widhar Pahlevi (Postgraduate Program Merdeka University, 2019)
This study aims to examine the sensitivity of the dollar exchange rate of the dollar (USD), inflation rate, SBI and the money supply against the Composite Stock Price Index. The study sample used Monthly data in the period January 1, 2008 to January 1, 2018, which data was obtained from the monthly report of Bank Indonesia. The research method used is a quantitative approach, namely Error Correction Model (ECM) with E-Views software. The results showed that the dollar (USD) exchange rate was sensitive to the Composite Stock Price Index, SBI was not sensitive to the Composite Stock Price Index, the money supply was sensitive to the Composite Stock Price Index and the inflation rate was sensitive to the Composite Stock Price Index DOI: https://doi.org/10.26905/afr.v2i1.3018